The effect of decision fatigue on surgeons' clinical decision making. (25th July 2019) - Persson, Emil; Barrafrem, Kinga; Meunier, Andreas; Tinghög, Gustav
Abstract: The depleting effect of repeated decision making is often referred to as decision fatigue. Understanding how decision fatigue affects medical decision making is important for achieving both efficiency and fairness in health care. In this study, we investigate the potential role of decision fatigue in orthopedic surgeons' decisions to operate, exploiting a natural experiment whereby patient allocation to time slots is plausibly randomized at the level of the patient. Our results show that patients who met a surgeon toward the end of his or her work shift were 33 percentage points less likely to be scheduled for an operation compared with those who were seen first. In a logistic regression with doctor‐fixed effects and standard errors clustered at the level of the doctor, the odds of operation were estimated to decrease by 10.5% (odds ratio = 0.895, p  < .001; 95% CI [0.842, 0.951]) for each additional patient appointment in the doctors' work shift. This pattern in surgeons' decision making is consistent with decision fatigue. Because long shifts are common in medicine, the effect of decision fatigue could be substantial and may have important implications for patient outcomes.